2017
DOI: 10.1016/j.elecom.2017.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Titanium vanadium nitride electrode for micro-supercapacitors

Abstract: International audienceHere we report on the synthesis of binary transition metal nitride electrodes based on titanium vanadium nitride (TiVN) thin films. These films were deposited by a method compatible with micro-electronic processes which consists of DC co-sputtering of vanadium (V) and titanium (Ti) targets. TiVN films with different Ti/V ratio were deposited. A dependence of the capacitance and the cycling stability with the Ti/V atomic ratio in the films was established. While V rich sample exhibits a Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(38 citation statements)
references
References 21 publications
0
34
0
Order By: Relevance
“…Generally, to enhance the storage performance of VN, strategies such as nanostructuring [ 18 , 19 , 20 , 21 ] and hybridization [ 22 , 23 , 24 ] have been employed. The hybridization approach involves carbon-based hybrids [ 21 , 25 , 26 ] and carbon-free hybrids [ 27 , 28 ]. For the VN-carbon-based hybrids electrodes, tremendous advancement has been realized [ 29 , 30 , 31 ], whereas carbon-free VN-based hybrids are still at their starting stage [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, to enhance the storage performance of VN, strategies such as nanostructuring [ 18 , 19 , 20 , 21 ] and hybridization [ 22 , 23 , 24 ] have been employed. The hybridization approach involves carbon-based hybrids [ 21 , 25 , 26 ] and carbon-free hybrids [ 27 , 28 ]. For the VN-carbon-based hybrids electrodes, tremendous advancement has been realized [ 29 , 30 , 31 ], whereas carbon-free VN-based hybrids are still at their starting stage [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the Mo 2 N nanobelts, which are porous, showed a high specific capacitance of 160 F/g, high rate capability, and good cyclic stability even at high scanning rates of 100 mVs −1 as a supercapacitor electrode material. Achour et al (2017) reported that a titanium vanadium nitride (TiVN) electrode can be used as an electrode material for microsupercapacitors. A TiVN electrode exhibited an areal capacitance value of 15 mF cm −2 at 2 mVs −1 with extraordinary capacitance retention of more than 99% after 10,000 cycles.…”
Section: Supercapacitorsmentioning
confidence: 99%
“…Lithium-ion batteries (LIBs) have become a topic of international research due to their long cycling lifetime, high working voltage, high energy density, high rate capability, and environment-friendliness [4,5]. It could be an important complement for the insufficient of the other power sources, for instance, supercapacitors and fuel cells [6,7,8]. However, commercial graphite is hard to adapt to the demand of widely application duo to the slow Li + diffusion rate and the formation of solid electrolyte interface (SEI) [9].…”
Section: Introductionmentioning
confidence: 99%